A case study of corporate social investment: employing people with intellectual disabilities - Pillay, Jayalakshmi (Rhodes University, Faculty of Commerce, Rhodes Business School, 2011)
This research was undertaken within the broader concept of Corporate Social Investments and how this concept is integrated within the context of staff retention and what this means for business and creating employment opportunities for people with disabilities. Illustrated through the description of CSI literature and intending to explain the link between CSI and employee retention, research questions presented as part of the outcomes for the research examines notion that there is a relationship between Corporate Social Investment and Employee Retention. Reference to the case study "Rhodes / Kuyasa Partnership" illustrates how such partnerships attempt to create opportunities for the community, the organisation, people with disabilities and employees at large. The case study was written to be used as a teaching case study in the context of Human Resources, Business Sustainability and Corporate Social Investment. The effectiveness and viability of the Kuyasa / Rhodes partnership will highlight acceptance and or non acceptance of people with disability by the non-disabled workforce. This case study will highlight CSI linkages that lead to staff retention, higher job satisfaction, lower turnover of staff, enhanced community engagement, creating opportunities that accommodate people with special needs, developing models that can be replicated in other organisations, creating additional opportunities for existing staff. Metcalf (2008:61) suggests that organisations need to ensure that the leadership and organisation culture within organisations is appropriate to engage staff with disabilities and non-disabled staff, and that their most senior managers demonstrate their commitment to develop, and help others develop, in the same way. The Kuyasa Rhodes Partnership may have started off as a Retention Strategy, however has given rise to a social initiative that can be replicated in other enabling organisations. The case study material was acquired through one on one interviews, and a focus group session on the effectiveness with the retention of such employees with intellectual disabilities, internship and mentoring issues, and as well as issues such as affirmative action, and the benefits and shortcomings of staff retention to the organisation. Key stakeholders interviewed for this case study expressed differing view -points, and in particular the benefits and shortcomings of this initiative. The Rhodes Kuyasa initiative appears to have achieved some success in enabling young adults / learners to work in a mainstream working environment by developing employment skills and life skills, and by improving their employment opportunities. Factors critical to the continuation of such initiatives included: the close involvement with both partners (Rhodes and the Kuyasa Special School), the sensitive treatment of the learners, and creating internal departmental partnerships within the Rhodes environment. A selected group of ten learners were mentored and provided with full time employment within the industrial Campus Food Services facility. Discussion that was highlighted in the case study must give consideration to a more investigative approach into overcoming the barriers of discrimination in the workplace and the major barriers to skills development. These have highlighted a number of relatively consistent themes around what were the successful and unsuccessful strategies. Integration of people with disabilities within the Rhodes University service areas has had positive effects for the disabled learner and employee workplace. People with disabilities indicated on how having mainstream employment allowed them to be independent, have a purpose in life and enhance their self worth in their communities and place of employment. Furthermore, being employed had positive repercussions on the person's co-workers. By demonstrating their competence, people with disabilities have had significant impact on other people's attitudes to disabled persons. Discussions held with the Principal of the Kuyasa Specialised School highlighted the need for crucial planning within special schools for disabled people in the area of transition from school to skills development and work. Skills development guidance is important in ensuring a choice of relevant interventions and obtaining the necessary information. Some staff expressed frustration at being with co-workers who questioned their presence and placement in the kitchen environment. Even though the disabled person was suitably placed they faced stereotypical behaviour and attitudes from their co-workers on what people with disabilities can or cannot do. Staff with intellectual disabilities commented that their co-workers see them as needing constant attention and care and not being capable of working. Some of the staff with disabilities had to work much harder to be recognised by their co-workers and supervisors. Currently few people with disabilities seem to be receiving career guidance while at school, as reflected in the case studies. One person with an intellectual disability described how the intervention of developing a comprehensive school leaving plan, which was then implemented by the school, allowed for good transition from school to Rhodes University. The role of personal factors such as life skills, personal motivation, the desire for personal achievement and a positive attitude were common themes that came out of the focus group. Initiatives to ensure that people accept themselves, their circumstances and are able to express their desires and realise their dreams are important factors. In addressing the barriers, co-worker attitudes make a big difference to how effectively the disabled person is able to participate in the training and employment. The future focus must be enabling and in line with successes and failures in the areas of employee integration in the workplace, life-skills development for people with disabilities. A clear career guidance plan should be developed for all disabled children before they leave school. This plan should include provision of adequate information on different career options and training. The negative attitudes of co-workers and supervisors should be changed by providing training support to ensure that they feel confident to meet the needs of disabled staff. Employers should be providing support and information on how to meet the needs of disabled employees. People with intellectual disabilities are an integral part of the South African population. Business and social enterprises need to have a focused inclusive strategy to integrate people with intellectual disabilities within the South African society to ensure equity and diversity awareness. Working with people with intellectual disabilities has been the focus of this research to ensure long term sustainable employment, CSI and Employment equity. Integrating Corporate Social Investment policies with Human Resources Equity policies are important factors in ensuring that people with intellectual disabilities are a fundamental focus in recruitment and retention strategies within business and social enterprises. Initiatives such as the Kuyasa / Rhodes Partnership are attempting to align to the overall objectives of incorporating people with intellectual disabilities into mainstream work, in particular, with the objective of incorporating people with disabilities in some accessible sections within the organisation. This contributes to the Rhodes University Campus Food Services becoming an example of excellence in the CSI and employee retention field. It is hoped that this teaching case study will make an important contribution to students learning about sustainable business practices, and for business focusing on employment recruitment and retention strategies to integrate people with intellectual disabilities within their organisations.
Keywords: Kuyasa Special School (Grahamstown, -- South Africa); Rhodes University -- Employees; Social responsibility of business -- South Africa; People with mental disabilities -- Employment -- South Africa; Employee retention -- South Africa; Industrial relations -- South Africa; Vocational guidance -- South Africa